THERAPEUTIC MANAGEMENT OF ODONTOGENIC KERATOCYST: FROM SIMPLE ENUCLEATION TO ADJUVANT TECHNIQUES (International Seven Journal of Multidisciplinary, 2026)
Odontogenic Keratocyst (OKC) is a lesion of odontogenic origin recognized for its aggressive biological behavior and high recurrence rate, making its therapeutic management a significant clinical challenge. In this context, several surgical approaches have been proposed over time, ranging from conservative methods such as simple enucleation and marsupialization to more aggressive techniques associated with adjuvant treatments. This study aims to review the therapeutic management of OKC, analyzing the main surgical techniques currently employed and the most effective adjuvant methods in reducing recurrence rates. The literature demonstrates that simple enucleation is associated with higher recurrence rates. On the other hand, the association of enucleation with adjuvant techniques such as peripheral ostectomy, chemical cauterization with Carnoy’s solution, and cryotherapy with liquid nitrogen has proven to be more effective in eliminating epithelial remnants and satellite cysts, significantly reducing lesion recurrence and providing better clinical outcomes.